The effect of cavity disinfectants on the micro-shear bond strength of dentin adhesives - Elkassas, Dina Wafik; Fawzi, Elham Mostafa; El Zohairy, Ahmed (European Journal of Dentistry, 2014)
Objectives: This study was carried out to examine the effect of application of four different disinfecting agents on the micro-shear bond strength (μ-SBS) of an etch-and-rinse and self-etch adhesive systems. Materials and Methods: One hundred flat dentin surfaces of human molars were produced by wet grinding the buccal surfaces. Specimens were randomly assigned to five groups according to the disinfectant used: Group I: Control (no disinfectant); Group II: 5.25% sodium hypochlorite based; Group III: 2% chlorhexidine based (Consepsis), Group IV: 0.1% benzalkoniumchloride based (Tubulicid red) and Group V: 3% doxycycline based (Biopure, MTAD). Specimens were bonded using either Adper Single Bond 2 or Clearfil S3 Bond, which were employed according to the manufacturer's instructions. Resin composite microcylinders were bonded using Tygon® tubes for μ-SBS testing. The modes of failure were noted after visual examination using a binocular stereomicroscope at ×25 magnification. Failures were classified as adhesive, or mixed. μ-SBS results were analyzed using two-way ANOVA followed by Tukey's post-hoc test. Results: Dentin disinfectants tested significantly negated the bonding of Adper Single bond 2 and the groups were ranked; Group I > Group V = Group IV > Group II = Group III, meanwhile they enhanced significantly the μ-SBS values upon using Clearfil S3 Bond and were ranked; Group II > Group III = Group IV = Group V > Group I. Most failures were adhesive with the Adper single bond adhesive system. Mixed modes of failure were evident with Clearfil S3 bond. Conclusions: The disinfectants tested should not be used with Adper Single Bond 2 when applied before the etching step, However they could be used safely prior to bonding with Clearfil S3 Bond.
Keywords: Benzalkonium chloride; chlorhexidine; doxycycline; sodium hypochlorite